Disharmony in the Concept of the Death Penalty between the National Criminal Code and the Anti-Corruption Law - Patrick Yehezkiel Bukanaung; Sri Astutik; Moh Taufik; Renda Aranggraeni (UNIVERSITAS PAKUAN, 2026)
This study examines the disharmony in the concept of the death penalty between the National Criminal Code and the Anti-Corruption Law in Indonesia. Article 2, paragraph (2) of the Anti-Corruption Law permits the imposition of the death penalty under certain circumstances, while Article 100 of the National Criminal Code positions the death penalty as an alternative punishment with a probationary period of ten years. This difference creates a normative conflict and raises legal uncertainty in the implementation of criminal law policies, particularly in corruption cases. The purpose of this study is to analyse the differences in the regulation of the death penalty and its implications for the Indonesian criminal justice system. This research is a normative legal study with a descriptive-analytical approach, using secondary data collected through library research and analysed qualitatively. The results indicate that the inconsistency between the two regulations reflects a lack of harmonisation in criminal law reform, potentially leading to differing interpretations and applications of the death penalty in corruption cases. Therefore, legal harmonisation is necessary to ensure legal certainty, justice, and consistency within the Indonesian criminal justice system. Keywords: Death-Penalty, National-Criminal-Code, Anti-Corruption, Norms, Criminal.